Interpreter training in Malaysia: Possibilities for the next millennium - Ibrahim, Zubaidah (Journal of Modern Languages, 1998)
This paper sets the scene for some preliminary research into the state of the legal interpreting service and the perceptions of court interpreters in Malaysia at the close of the 20th century.